The Dynamics Beyond Counter Terrorism Measures in the Indo-Pacific [Dinamika di Luar Upaya Melawan Terorisme di Indo Pasifik] - Samti Wira Wibawati; Marina Ika Sari; Yuli Ari Sulistyani (Sekretariat Jenderal DPR RI, 2019)
The Indo-Pacific is a conceptual idea aimed at enhancing economic connectivity and security among states in the Indo-Pacific region. In line with the high interest from many Indo-Pacific states, security problems like terrorism are of common concerns that need to be addressed. Various existing security cooperation mechanisms have been established to solve this latent problem. However, these mechanisms have not been able to decrease the number of terrorist acts in the region. This study discusses the urgency of terrorism issues in the Indo-Pacific region with the current security cooperation mechanisms. This research uses qualitative method which allows the researchers to describe and explore the observed phenomenon. Using the theory of international cooperation, this research found that it is necessary to recalibrate the existing security cooperation or to focus on making a new and integrated mechanism in the Indo-Pacific region.AbstrakIndo-Pasifik adalah ide konseptual yang bertujuan untuk meningkatkan konektivitas ekonomi dan keamanan di antara negara-negara yang berada di kawasan Indo-Pasifik. Sejalan dengan banyaknya kepentingan berbagai negara di Indo Pasifik, masalah keamanan seperti terorisme perlu menjadi perhatian bersama. Berbagai mekanisme kerjasama keamanan telah dibentuk untuk menangani masalah laten ini. Namun, mekanisme kerjasama keamanan yang ada belum mampu mengurangi angka tindak terorisme di kawasan. Studi ini membahas tentang urgensi masalah terorisme di kawasan Indo-Pasifik dengan mekanisme kerjasama keamanan yang sudah ada. Penelitian ini menggunakan metode kualitatif dimana para peneliti dapat menggambarkan dan mengeksplorasi fenomena yang diteliti. Dengan menggunakan teori kerjasama internasional, penelitian ini menemukan bahwa perlu untuk mengkalibrasi ulang kerjasama keamanan yang sudah ada atau fokus pada pembuatan mekanisme baru dan terintegrasi di kawasan Indo-Pasifik.